2023
DOI: 10.1017/jfm.2023.244
|View full text |Cite
|
Sign up to set email alerts
|

Linear response analysis of supersonic turbulent channel flows with a large parameter space

Abstract: In this work, the linear responses of turbulent mean flow to both harmonic and stochastic forcing are investigated for supersonic channel flow. Well-established universal relations are utilized to obtain efficiently the mean profiles with a large parameter space, with the bulk Mach number up to 5 and the friction Reynolds number up to $10^4$ , so a systematic parameter study is feasible. The most amplified structure takes the form of streamwise velocity and temperature streaks forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…Through the comparison of Figs. 6(b) and 6(c), most vortices populate around low-speed streaks since low-speed streaks are recognized to be induced by the moving hairpin leg [50]. This close connection is also reported by Jiménez and Pinelli [51] and Ringuette et al [52] in incompressible flows, and Pirozzoli et al [19] in a compressible turbulent boundary layer at Ma = 2.…”
Section: A Instantaneous Vortex Structuressupporting
confidence: 73%
“…Through the comparison of Figs. 6(b) and 6(c), most vortices populate around low-speed streaks since low-speed streaks are recognized to be induced by the moving hairpin leg [50]. This close connection is also reported by Jiménez and Pinelli [51] and Ringuette et al [52] in incompressible flows, and Pirozzoli et al [19] in a compressible turbulent boundary layer at Ma = 2.…”
Section: A Instantaneous Vortex Structuressupporting
confidence: 73%
“…This treatment is not arbitrary. On the one hand, T is typically considered as a passive scalar in incompressible wall turbulence Antonia, Abe & Kawamura 2009) and compressible wall turbulence at low Mach number (Chen et al 2023a;, just like g . On the other hand, T can strikingly influence the u field through the interactions between the momentum and energy equations in compressible wall turbulence, whereas g cannot.…”
Section: Diagnostic Tool: Spectral Linear Stochastic Estimation and C...mentioning
confidence: 99%
“…Such a scaling was proposed by Song et al [137] through deducing the GRA with fitted coefficients. Subsequently, closed ODEs were established by Song et al [138] and Chen et al [139], whose predictions of the mean velocity and temperature (and density) attain high accuracy. Notably, the Trettel-Larsson and total-stress-based transformations are used throughout, although they are not designed to work in the outer region.…”
Section: Closed Inverse Problemmentioning
confidence: 99%
“…The statistical characteristics of some decomposed modes satisfy the predictions of the attached-eddy model. Chen et al [139] investigated the linear responses of turbulent mean flow to both harmonic and stochastic forcings for supersonic channel flow, and found that the scale features of the most amplified streamwise velocity structures are in tune with those of incompressible wall turbulence; see Fig. 19(a) and (c).…”
Section: Attached Eddies In Compressible Wall-bounded Turbulencementioning
confidence: 99%
See 1 more Smart Citation